Nasilje v družini in strateški rituali poročanja - Luthar, Breda (Družboslovne razprave, 2007)
The article explores the representation of domestic violence in quality daily newspapers and on a news and current affairs programme on Slovenian television. Its emphasis is on the formal issues of the media's representation of violence, particularly on the generic aspects of chronicles in the daily press and on the episodic news story on television news. The authors argue that the journalistic representation of domestic violence uses 'factism' as a key strategic ritual of reporting which results in the decontextualisation, psychologisation and individualisation of the problem of violence. Police and the judiciary act as standard bureaucratic sources which serve to authenticate and verify the journalistic discourse. The main feature of the news on domestic violence on television is the episodic account of events in the news programme, the standard framing of the problem within the framework of conflict between political parties and the melodramatic representation of violence in the current affairs programme. The melodramatisation of violence in turn results in the decontextualiaation and individualisation of the problem of domestic violence that is conventionally interpreted as being outside of the structural sources of violence, such as class differentiation and the performance of hegemonic masculinity.
Keywords: Družina; Family; Nasilje; Violence; Moškost; Masculinity; Hegemonism; Hegemonizem; Mass media; Množični mediji; Poročanje; Reporting; Slovenia; Slovenija; nasilje v družini; kronika; Krónika